Análise de complexidade de códigos turbo utilizando as treliças mínima e seccionada - Moritz, Guilherme Luiz (2012)
We present a technique for reducing the turbo decoding complexity based on minimal and sectionalized trellises. A novel complexity metric is proposed and the complexity of all possible sectionalizations for some selected codes is evaluated. We use the minimal trellis representation proposed in (MCELIECE, 1996) for BCJR decoding and conclude that one can find less complex sectionalizations (when compared to the conventional trellis) which show small or none performance degradation.